Factors influencing the intention of state foundation loan recipients to payback the education loan - Nurul Farhanah, Mohd Idres; Hasnah, Haron; Ishak, Ismail (Penerbit UMP, 2019)
The issues of loan repayment are still existing until today. One of the state foundations has reported the number of recipients that has not paid their loan are higher than the recipient who has done the repayment. Therefore, the main objective of this study is focusing on the factors that influences the recipient to pay back the loan. 48 questionnaires were distributed to the state foundation’s loan recipients and a small interview were also conducted. Findings showed that the respondents had the intention to repay their loan as they were aware of their responsibilities especially the recipient that have high integrity. However, the inability to secure a good paying job is one of the reasons why they are not able to do so. Parental influence was found to be significant in influencing the loan recipients to repay their loan. It is suggested that the state foundation should increase the sense of responsibility among loan recipients to pay their loan and reminders should be given to their parents in order to convince their children to repay the loan.